1012. Characterization of Antibiotic Superutilizers in the Inpatient Setting - Burns, Jonathan (Open Forum Infect Dis, 2019)
BACKGROUND: Inappropriate use of antibiotics is a major public health concern that contributes to increased antibiotic resistance, adverse effects, and healthcare costs. Little is known about the highest utilizers, or superutilizers, who may be appropriate targets for antibiotic stewardship efforts. The purpose of this study was to characterize superutilizers at an academic hospital. METHODS: All adult patients who were admitted to the Hospital of the University of Pennsylvania and received at least one day of antibiotics between July 1, 2017 and June 30, 2018 were identified. All inpatient administrations for systemic antibacterial agents were identified. Antibiotics given in procedural areas and the emergency department were excluded, as were any antifungals and antivirals. Usage was reported as days of therapy (DOT). We compared the demographics and DOT among the superutilizers (defined as the top 1% of patients) to different groupings of the rest of the population. RESULTS: Overall, 13,559 patients (and 183,082 DOT) were included in the analysis, including 136 superutilizers. The superutilizers received 15% of the total antibacterial DOT and a median of 56 DOT during the 12-month period. (table) CONCLUSION: Inpatient antibiotic use is unevenly distributed across the population. Higher meropenem and sulfamethoxazole/trimethoprim DOT suggest that treatment of multidrug-resistant organisms and opportunistic infection prophylaxis are more common in the superutilizer group. Additional study is needed to determine whether antimicrobial stewardship efforts could impact antibiotic use in the superutilizer population. [Image: see text] DISCLOSURES: All authors: No reported disclosures.